EFFECTIVENESS OF REARING AND FATTENING OF LOW-WEIGHT PIGLETS DUE TO CHANGES IN THEIR FEEDING SYSTEMS - Igor MOISEI; Mykola POVOD; Oleksandr MYKHALKO; Mykola POVOZNIKOV; Bogdan GUTYJ; Yulia IEVSTAFIIEVA; Vita BUCHKOVSKA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article contains the results of a study on the conservation, growth dynamics from birth to slaughter and economic efficiency of growing and fattening pigs depending on their live weight at birth and different feeding systems during the production cycle. It was found that piglets with a birth weight of just under one kilogram at weaning at 21 days of life had 30.3 % lower average and absolute gains, 29.4 % less live weight at this time and 4.5 % poorer maintenance in the post-weaning period compared to piglets whose live weight at birth was at the level of the line standard. During the suckling period, the weight difference between the animals at the beginning and end of the suckling period increased by 3.5 % in favor of the heavy piglets. During the rearing period and in the previous suckling period, animals with a lower birth weight had a 2.9 % worse preservation, grew 13.8 % slower and had a 13.8 % worse absolute weight at the end of rearing and at this time had a 17.7 % lower live weight and a 16.2 % worse feed conversion ratio at the same daily consumption, compared to animals born with a normal live weight. With the same costs for piglets with different birth weights and in the weaning phase, the difference according to this indicator is 8.4% in the rearing phase, 16.7% in the fattening phase and 13.2% for the entire production cycle in favor of the animals with normal birth weights. At the same time, these animals have a 3.2 % lower sales value, which leads to a 22.3 % lower income and a 31.4 % lower profitability of rearing and fattening a pig.